2016
DOI: 10.1111/bjop.12187
|View full text |Cite
|
Sign up to set email alerts
|

The role of magical thinking in forecasting the future

Abstract: This article explores the role of magical thinking in the subjective probabilities of future chance events. In five experiments, we show that individuals tend to predict a more lucky future (reflected in probability judgements of lucky and unfortunate chance events) for someone who happened to purchase a product associated with a highly moral person than for someone who unknowingly purchased a product associated with a highly immoral person. In the former case, positive events were considered more likely than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Although causal inferences regarding the effect of education are difficult, researchers can still explore the causal assumptions behind the role of control in cynicism development. For example, manipulating perceived constraints (e.g., see Stavrova & Meckel, 2017 ) to examine their effect on cynical beliefs might be the first step on this way.…”
Section: Discussionmentioning
confidence: 99%
“…Although causal inferences regarding the effect of education are difficult, researchers can still explore the causal assumptions behind the role of control in cynicism development. For example, manipulating perceived constraints (e.g., see Stavrova & Meckel, 2017 ) to examine their effect on cynical beliefs might be the first step on this way.…”
Section: Discussionmentioning
confidence: 99%
“…While experimental manipulations of poor health seem implausible, future studies might focus on testing/establishing the causality behind the effect of perceived constraints as a mechanism linking health deterioration and cynicism. In fact, experimental manipulations of perceived control are frequently reported in psychological literature (Stavrova & Meckel, 2017;Whitson & Galinsky, 2008) and might represent a promising tool for establishing the causal role of perceived constraints in cynicism development.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…A growing literature within psychology has demonstrated that beliefs in contagion are quite pervasive and can influence people's attitudes and behaviors across a variety of contexts. Contagion beliefs have been shown to affect purchase decisions in: retail settings (Argo, Dahl & Morales, 2006;2008;Morales & Fitzsimons, 2007); preferences for luxury goods (Newman & Dhar, 2014); auction behavior and collecting (Newman & Bloom, 2014;Newman, Diesendruck & Bloom, 2011); desires to keep sentimental possessions (Grayson & Shulman, 2000); gambling decisions (Mishra, Mishra & Nayakankuppam, 2009;Wohl & Enzle, 2002); predictions about the future (Stavrova & Meckel, 2016); ability and performance (Kramer & Block, 2014;Lee, Linkenauger, Bakdash, Joy-Gaba & Profitt, 2011); preferences for sacred land (Rozin & Wolf, 2008); and even the choice of organ transplant donors (Hood, Gjersoe, Donnelly, Byers & Itajkura, 2011;Meyer, Leslie, Gelman & Stilwell, 2013).…”
Section: Introductionmentioning
confidence: 99%